KERAJAAN ALLAH DALAM INJIL MATIUS PERUMPAAN TENTANG SEORANG PENABUR - Alfinia Tecuari; Ausvina; Enjelia; Sarmauli (Pondok Pesantren Baitul Qur`an Sambas, 2024)
This journal aims to analyze the role and meaning of the parable of a sower in God's kingdom, especially that found in the Gospel of Matthew 13:1-23. The scattering in the Gospel of Matthew describes Jesus' teaching about the kingdom of God and how important it is for people to respond to the message of the kingdom of God and what is most important can be accepted and practiced by believers.